Analysis of influencing factors of washed microbiota transplantation in treating patients with metabolic syndrome - Lin, De-Jiang; Hu, Dong-Xia; Wu, Qing-Ting; Huang, Lin-Gui; Lin, Zi-Han; Xu, Jia-Ting; He, Xing-Xiang; Wu, Lei (Frontiers in Nutrition, 2025)
Background and aimsMetabolic Syndrome (MS) is a cluster of metabolic abnormalities closely associated with hypertension, diabetes, hyperlipidemia, obesity, etc. Our previous research indicated that fecal microbiota transplantation (FMT) could improve MS, but the factors influencing the efficacy of washed microbiota transplantation (WMT) in treating MS patients remain unclear. The objective of this study is to analyze the influencing factors of WMT in treating MS patients.MethodsThe clinical data and influencing factors related to MS patients were collected retrospectively. Not only the changes in body mass index [BMI = weight (kg)/height (m)2], blood glucose, blood lipids, and blood pressure were analyzed, but also the influencing factors of WMT in treating MS patients were carried out based on Logistic Regression. The 16S rRNA gene amplicon sequencing was performed on fecal samples before and after WMT treatment.ResultsA total of 210 patients were included, including 68 patients in the WMT group and 142 patients in the drug treatment (DT) group. WMT had a significant improvement and ASCVD downregulation effect on MS patients, and 42.65% of MS patients removed the label of MS after WMT treatment. Independent influencing factors for treating MS patients through WMT include age < 60 years old, high smoking index, infection, single donor selection, single-course WMT treatment, and having hypertension, diabetes, or obesity. WMT treated MS patients by maintaining the balance of gut microbiota.ConclusionsWMT has a significant effect in improving MS and downregulating ASCVD risk stratification. The therapeutic effect of WMT on MS patients is closely related to their age, smoking index, infection, chronic disease status, donor type, and WMT courses. Therefore, we can improve the efficacy of WMT by reducing independent influencing factors that affect gut microbiota homeostasis.